Performance of colored pepper cultivars under different concentrations of nutrient solution - Evangelista de Souza, Almir Rogerio; Oliveira, Jailson; Prates, Fabiano Barbosa de Souza; Tartaglia , Francilene de Lima; Nascimento, Denisson Lima do; Veloso, Cássio Laurentino (Comunicata Scientiae, 2022)
Knowledge on the nutritional requirement of the crop under cultivation systems adapted to local realities, in addition to the adequate availability of nutrients in nutrient solution, is of fundamental importance both for plant growth and for the production of quality fruits. Thus, the objective of this study was to evaluate the production performance of colored bell pepper cultivars in an open hydroponic system under different concentrations of nutrient solution. The experiment was carried out in a greenhouse at IFAL, Piranhas Campus, in a completely randomized experimental design with four replicates and in split plots, with plots containing three concentrations of nutrient solution (75%, 100% and 125%) and subplots containing three bell pepper cultivars (All Big, Sucesso and Beti-R). Concentration of nutrients at 75% of the standard nutrient solution differed from the other concentrations for plant height, stem diameter, leaf area and fresh and dry mass of the plant. The total number of fruits and number of marketable fruits were higher in the Beti-R and Sucesso hybrids when subjected to concentrations of 75% and 100%, respectively. The total yields of the Beti-R and Sucesso hybrids were higher at the concentration of 75%, with maximum values of 24.19 t ha-1 and 17.11 t ha-1, respectively. The concentration of 100% of the standard solution promoted higher results for the All Big cultivar.